2016
DOI: 10.3390/su8100999
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Albedo Increase to Mitigate the Urban Heat Island in Terni (Italy) Using the WRF Model

Abstract: Abstract:The impacts of the urban heat island (UHI) phenomenon on energy consumption, air quality, and human health have been widely studied and described. Mitigation strategies have been developed to fight the UHI and its detrimental consequences. A potential countermeasure is the increase of urban albedo by using cool materials. Cool materials are highly reflective materials that can maintain lower surface temperatures and thus can present an effective solution to mitigate the UHI. Terni's proven record of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 41 publications
0
45
0
Order By: Relevance
“…Sustainability 2017, 9, 312 3 of 17 and there has been an obvious increasing trend in the mean air temperature. The highest monthly average temperature is 23.1 °C in July and the lowest is −15.6 °C in January.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Sustainability 2017, 9, 312 3 of 17 and there has been an obvious increasing trend in the mean air temperature. The highest monthly average temperature is 23.1 °C in July and the lowest is −15.6 °C in January.…”
Section: Study Sitementioning
confidence: 99%
“…Thus, it has become a major research focus in urban climatology and urban ecology since first reported in 1818 [16]. To have a better understanding of the UHI effects is very important for providing a scientific basis for future climate mitigation and urban planning [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Other techniques to study the UHI and simulate the urban climate are present in the literature such as Research and Forecasting (WRF) and ENVI-met. Morini, Touchaei, Castellani, Rossi, and Cotana (2016) employed the WRF coupled to multi-layer urban canopy model (UCM) and building energy model (BEM) to study the impact of albedo increase to mitigate the UHI. Shen, Chow, and Darkwa (2013) used the ENVI-met to simulate urban climate parameters to evaluate the influence of microclimatic design on mitigating the UHI effects.…”
Section: Introductionmentioning
confidence: 99%
“…• significant economic benefits for the private side and energy/environmental benefits for the collective side; • better local quality of cities and more livable outdoor and indoor conditions; and • opportunities to address the impacts and challenges of urban heat islands [17], as well as to achieve the targets of sustainability promoted by the countries at international levels.…”
Section: Introduction: Importance Of Large-scale Energy Retrofit Of Tmentioning
confidence: 99%